Palladium and copper mediated cross couplings using dialkylphosphites - Fraser, Jamie (2013)
Described herein are synthetic methodologies using palladium- and copper-mediated cross coupling reactions involving dialkylphosphites. Chapter 1 discloses two methods for producing alknylphophonates. The first is a novel palladium mediated cross coupling of alkynylbromides with dialkylphosphites. The second is an improvement of a known aerobic copper mediated cross coupling using terminal alkynes and dialkylphosphites. Chapter 2 discloses a novel aerobic copper mediated amide synthesis method. Chapter 3 discloses a novel aerobic copper mediated phosphoramidate synthesis method. All of the above developed methodologies were found to produce their respective products in acceptable yields and tolerate a wide range of functionality. The experimental section comprises the practical methods for effecting the above reactions and the experimental data for all of the compounds presented herein.